Pengembangan Instrumen Tes Kemampuan Berpikir Kritis Pada Mata Pelajaran IPAS Sekolah Dasar - Desi Dwi Prastiti; Endang Susilaningsih (Jurnal Evaluasi Pendidikan, 2026)
This study aimed to develop a FRISCO-oriented (Focus, Reason, Inference, Situation, Clarity, Overview) critical thinking test instrument for fourth-grade elementary students in IPAS learning on Indonesian cultural diversity material. The study employed a Research and Development (R&D) method using the ADDIE model. The population consisted of elementary school students, while the sample involved 20 fourth-grade students of SDN Kejawan Putih I/243 Surabaya selected through purposive sampling. Research instruments included validation sheets and a 20-item multiple-choice critical thinking test. Content validity was assessed by three subject experts and two classroom teachers. Findings showed a content validity score of 0.89 (very valid) and a reliability coefficient of 0.842 (high category). Empirical testing indicated that 80% of items had moderate difficulty and good discrimination power, demonstrating that the instrument is feasible, reliable, and effective for measuring students’ critical thinking skills.